Fluid dynamics of planetary differentiation - Deguen, Renaud; Huguet, Ludovic; Landeau, Maylis; Lherm, Victor; Maller, Augustin; Wacheul, Jean-Baptiste (Comptes Rendus. Physique)
The basic structure of the terrestrial planets—an iron-rich metallic core surrounded by a silicate mantle—was established during their accretion, when widespread melting allowed the metal and silicate phases to separate. The transfer of chemical elements and heat between the metal and silicate that occurred during this period is critical for the composition and initial temperature of the core and mantle, and has important implications for the long-term evolution and dynamics of the planets. After having summarised the main observational constraints on core-mantle differentiation, the article follows the sequence of processes that led to the formation of planetary cores, focusing on the contributions of laboratory fluid dynamics experiments to our understanding of these processes, and discussing the relevance and limitations of this approach to this problem. We first focus on the dynamics of planetary impacts, using laboratory experiments to illustrate and quantify the impact and cratering processes and the resulting metal phase dispersion. We then consider the two-phase flow that follows an impact, when a molten impactor core falls by buoyancy in a magma ocean. The model of miscible turbulent thermal, which we argue is a good reference model for the post-impact flow, is presented. We then discuss how additional factors—immiscibility and fragmentation, inertia inherited from the impact, Coriolis force, sedimentation—affect the predictions of this model, and discuss the extent of chemical equilibration. Finally, a last part of the article is devoted to the migration of the metal phase through a solid part of the mantle.